ANALISIS TINGKAT PERSAINGAN USAHA CAFE BOX KELURAHAN SUDIANG KECAMATAN BIRINGKANAYA KOTA MAKASSAR - ALDI INDRHAWARDANA; MUHAMMAD HASAN; MUSTARI; MUH IHSAN SAID; MUHAMMAD DINAR (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
This study aims to determine the level of competition in the cafe box business, Sudiang Village, Biringkanaya District, Makassar City. This research is a descriptive qualitative research with two data sources, namely primary data and secondary data. The selected research objects are Cafe Underbox and Cafe FA Tea. The data collection process uses interview techniques to several respondents and informants as well as observations and documentation related to research. Based on the results of research and data management, then: 1) Aspects of price, business competition both cafes determine the price of beverage products sold based on market prices by taking into account the costs and expenses of each cafe. 2) Product aspect, each Cafe has its own product focus based on the target market objective. 3) From the promotion aspect. Cafe underbox applies word of mouth or word of mouth promotion techniques. While Cafe FA Tea not only applies word of mouth promotion strategies but also utilizes social media platforms as an active promotional tool to support business development.